Labor Outsourcing in the Steelmaking Industry in Argentina: Companies of Ex-workers in Acindar Villa Constitución and Siderar Ensenada - María Alejandra Esponda; Julia Strada (Íconos, 2019)
Labor outsourcing as a business strategy that tends to increase flexibility and the precarization of the workforce, as well as weaken trade unions, has become worse since the mid-1970s. This has been the case not only in Argentina, but in Latin America and the world at large, with a strong impact since the 1990s. This article analyzes the comparative expansion of outsourcing since the subcontracting of ex-workers, taking into account two case studies in the steelmaking industry in Argentina: Cooperar 7 de Mayo en Acindar Villa Constitución and CIMET en Siderar Ensenada. Based on an interdisciplinary social anthropology, political science and political economy approach, this article reflects on the origins, trajectories, structural conditionings, and projections of these contracting businesses.